L1L5Together: Report of Workshop on Future Missions to Monitor Space Weather on the Sun and in the Solar Wind Using Both the L1 and L5 Lagrange Points as Valuable Viewpoints. Issue 5 (20th May 2017) - Hapgood, Mike
Abstract: The "L5 in Tandem with L1: Future Space Weather Missions Workshop" was held in London on 6–9 March 2017 to discuss technical and programmatic steps toward an operational system for monitoring space weather conditions on the Sun and in the solar wind. This system would exploit the viewpoints provided by the Sun‐Earth L1 and L5 Lagrange points—two locations where we can place spacecraft in quasi‐stable orbits with complementary views of solar and interplanetary conditions that could lead to adverse space‐weather impacts at Earth. This personal report summarizes the talks and discussions at the workshop—pulling out key issues of likely interest to a wider audience and important considerations on the route to an operational system at L1 and L5, a system that can help to protect societies around the world from the risks posed by space weather. Plain Language Summary: A workshop was held in London on 6–9 March 2017 to discuss technical and programmatic steps toward an operational system for monitoring space weather conditions on the Sun and in the solar wind. This system would exploit the viewpoints provided by two locations where we can place spacecraft in quasi‐stable orbits with complementary views of solar and interplanetary conditions. One location sunward of the Earth (L1) enables head‐on observations of Earth‐directed space weather, while the other location trails Earth in its orbit around the Sun (L5) and enables a side view of Earth‐directed space weather, a complementary view that makes for better space weather forecasts. This personal report of the meeting summarizes the talks and discussions at the workshop—pulling out key issues that the author believes will be interesting to a wider audience, as well as being important considerations on the route to an operational system at these two points (L1L5together), a system that can help to protect societies around the world from the risks posed by space weather. Key Points: "L5 in Tandem with L1 Workshop" held in March 2017 to discuss operational space weather monitoring from both L5 and L1 Lagrange points International collaboration is a pathway to deliver rich space weather monitoring with solar and solar wind observations at L5 and L1 Key challenges include deeper understanding of how specific observations lead to better forecasts and how forecasts deliver economic impact